Exhaled breath condensate purines correlate with lung function in infants and preschoolers. Issue 2 (21st May 2012) - Patel, Kavita; Davis, Stephanie D.; Johnson, Robin; Esther, Charles R.
Abstract Rationale Although airway inflammation begins early in life in children with chronic respiratory diseases, current methods to assess this inflammation are invasive and entail significant risk. Measurement of exhaled breath condensate (EBC) purines and other biomarkers offers a less invasive method to assess airway inflammation; however, the feasibility and utility of EBC biomarkers in young children has not been established. Methods EBC was collected from children <3 years old with cystic fibrosis or other lung diseases during clinically indicated infant pulmonary function tests (iPFTs). EBC concentrations of the purine biomarkers adenosine (Ado), adenosine monophosphate (AMP), and the dilution marker urea were measured using mass spectrometry. Results EBC was successfully collected (average volume 330 ± 170 µl) from preschool children (age 2.3 ± 0.8 years) in 15 of 17 iPFTs. No significant changes in oxygen saturation (96.9 ± 1.6 start, 96.8 ± 1.7 end, P = 0.389) or respiratory rate (35.2 ± 7.5 start, 34.6 ± 7.9 end, P = 0.443) were observed during collection. Ado and AMP were successfully measured in 13/15 samples [8 cystic fibrosis (CF)]. EBC AMP to Ado ratio (AMP/Ado) negatively correlated with forced expiratory volume at 0.5 sec (FEV0.5, r = −0.71, P < 0.01) and positively with the ratio of residual volume to total lung capacity (RV/TLC, r = 0.66, P = 0.015). These correlations remained statistically significant in the subset with CF. Conclusions EBC can be safely collected and analyzed in preschool children using commercially available equipment. The EBC AMP/Ado ratio correlates with measures of infant lung function and may be a less invasive means of monitoring airway inflammation in this population. Pediatr Pulmonol. 2013; 48:182–187. © 2012 Wiley Periodicals, Inc.